Sistem Perpustakaan Digital dan Administrasi Perpustakaan Dalam Meningkatkan Pelayanan Perpustakaan - Vikasari, Cahya (P3M Politeknik Negeri Cilacap, 2021)
Activities in the library The process of finding references will be difficult for users and with the Covid-19 pandemic condition, work from home is enforced, this will also have an impact on administration and services in the library. Development of a digitalization system and library administration in improving the services of the PNC library using the software development method of the system development life cycle and the system built on a web-based basis. The design uses the UML concept, system testing using the blackbox testing method, boundary value analysis, and system evaluation with the concept of end-user computing satisfaction. The purpose of this research is to build a library digitalization system and library automation that can assist the administrative process and service to users. The result of the research is a digitalization system that can provide information, namely references in the form of final project books and industrial internships in web-based libraries and independent circulation systems in libraries that will support library services more effectively and efficiently.